Analysis of Indonesia's Three Major Anthropogenic Pollutants Which Include Various Emission and Fuel Sectors in the 1990-2015 Period - Sunarno, S.; Purwanto, P.; Warsito, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
The rapid industrial growth and urbanization in Indonesia over the last two decades have resulted in a significant increase in air pollution, so it has caused a decrease in air quality. An air pollution inventory is needed to determine the level of air quality, emission sector, and the type of pollutant fuel. Air pollutant emission data were obtained from various sources, including Regional Emissions Inventory in Asia (REAS) V3.1, Database Emissions for Global Atmospheric Research (EDGAR) V4.3.2, and Community Emissions Data System (CEDS) V1.0. The data consists of 3 types of emitted pollutants (CO, NOX, and SO2) and two contributing factors (emission and fuel sectors). This study aims to compare data from the emission sources of the three air pollutants, determine the trend of changes in the emission of the three pollutants, and determine the main sectors and fuels that emit the three air pollutants. This research uses the literature study method to collect, visualize, and analyze data. The results showed that between 2005 and 2012, there was a downward trend in emissions in the industrial sector for CO, NOX, and SO2 gases, with the lowest point in August. This is because many industrial sectors have applied the principle of clean energy to reduce air pollution and create clean air. However, the transportation sector showed an increase in CO and NOX emissions and peaked in April and October. Furthermore, the SO2 emissions for the power generation sector fluctuated and peaked in July.